(untitled) (Salam International Academic Journal, 2011)
This article deals with the issue of "the importance of Hadith in the interpretation of the Holy Qur’an and legislation." The Almighty Allah made the Prophet (blessings and peace be upon him) an interpreter of the Holy Qur’an as well as a communicator of the message of Allah to His creation. The interpretation of the Holy Qur’an means to clarify its provisions; hence, the Muslims need to refer to the interpretation of the Prophet (peace be upon him) of the Holy Qur’an. The hadith explains the Quran in all respects, such as (Bayan al Mujmal) the clarification of the unclear, (Taqyeed al Mutlaq) the limitation of the absolute, (Tawdheeh ul Mubham) the clarification of the vague, (Takhsees al a’am) the specification of the unspecified, the removal of illusion and confusion, and the determination of (al Naskh) the amendment and (al Mansookh) the amended. It is impossible for a Muslim if he does not return to the interpretation of the Prophet (peace be upon him) of the Holy Quran to know the details of the pillars of Islam, such as prayer, almsgiving and pilgrimage, fasting, and others. Hadith—along with the interpretation of the Holy Quran—is an independent source of legislation as well, and the (Halal) and (Haram) prohibitions given in the talk are based on divine revelation, and from here it is from God Almighty.